Clinical pharmacokinetics of oxaliplatin in a hemodialysis patient with advanced gastric cancer. (2nd January 2021) - Maruta, Motofumi; Miyoshi, Takanori; Matsuo, Naomi; Yamashina, Takuya; Irie, Kenji; Tsuruta, Minako; Tsukada, Hiroko; Tsuruyama, Moeko; Nagano, Masahisa; Hiraki, Yoichi
Abstract : We administered FOLFOX (oxaliplatin (L-OHP) plus infusional 5-fluorouracil (5-FU) and leucovorin) to an hemodialysis (HD) patient with advanced gastric cancer (AGC), and investigated pharmacokinetics (PKs) and dialyzability of L-OHP. The patient was a 54-year-old Japanese man with a diagnosis of inoperable AGC. FOLFOX was instituted 3 h prior to the start of a 4 h HD period with the L-OHP and 5-FU doses reduced by 50% for the first cycle, and 30% reduced dose was administered for the second cycle. We performed an analysis of the PKs of L-OHP during these two cycles. Volume of distribution and area under the curve of the 30% reduced L-OHP dose were 56.7 L and 30.0 μg·h/mL, respectively. A dose reduction of L-OHP by 30%−50% may be advisable for the initial administration, given the need for careful administration of chemotherapy in HD patients, with particular attention to the development of hematological toxicities and neuropathy.